Novel perspectives on growth hormone regulation of ovarian function: mechanisms, formulations, and therapeutic applications - Yang, Shao; Luo, Wei; Sun, Yawei; Wang, Shan (Frontiers in Endocrinology, 2025)
Delayed childbearing has led to a continuous rise in the incidence of infertility because of social development and the evolving roles of women. Assisted reproductive technology (ART) has provided new opportunities for infertility treatment, such as the application of growth hormone (GH). GH regulates ovarian function through multiple pathways, improving follicular development and hormone secretion. However, traditional GH therapy is limited by issues such as low bioavailability and insufficient delivery efficiency. In recent years, drug delivery systems based on novel biomaterials have provided breakthrough solutions for the innovative application of GH in ART. This review summarizes the mechanisms by which GH affects ovarian endocrine function and focuses on the cutting-edge advancements in GH delivery systems with examination of the innovative applications of composite biomaterials in enhancing the therapeutic efficacy of GH. By analyzing the pharmacokinetic properties of novel formulations, the safety and long-term efficacy of their clinical applications can be evaluated. GH delivery systems based on novel biomaterials considerably improve the bioavailability and targeting of GH and could lead to innovative therapeutic strategies for preventing and treating ovarian dysfunction and related diseases. By integrating multidisciplinary research findings, we provide new insights into the field of reproductive medicine that could lead to theoretical and practical importance for promoting the innovative development of ART.